Can we know more about atherosclerosis in cyanotic patients with congenital heart disease—the potential role of sphingosine-1-phosphate? - Nartowicz, Sonia Alicja; Gabriel, Marcin; Janus, Magdalena; Cieślewicz, Artur; Malesza, Katarzyna; Bartczak-Rutkowska, Agnieszka; Lesiak, Maciej; Trojnarska, Olga (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsProgress in cardiology has extended the lifespan of patients with congenital heart defects (CHD). Cyanotic patients are exposed to typical diseases of adulthood, including atherosclerosis. Rheological changes typical of cyanosis affect the vascular endothelium's function and may promote atherosclerosis development. We assessed the endothelial function and its relationship to biochemical parameters, particularly sphingosine-1-phosphate, in cyanotic CHD patients.MethodA cross-sectional study including 36 adult CHD cyanotic patients [(12 males) (39 median, 19–73 years)] with arterial blood oxygen saturation less than 92% and 30 healthy controls [(11 males) (38.5 median, 26–59 years)] was performed. All patients underwent clinical examination, blood sampling, and ultrasonography, during which endothelial function was assessed using intima-media thickness (IMT) and flow-mediated dilatation (FMD).ResultsWe did not demonstrate any difference between CHD patients and the control group in the IMT complex and FMD. Patients with cyanosis are characterized by higher S1P serum levels (p = 0.04), lower ApoM (p = 0.04), and HDL concentrations (p = 0.02). Only FMD correlated positively with HDL cholesterol (p = 0.02) concentration. The IMT complex correlates positively only with BMI (p = 0.04). No factor was statistically significant in the multiple logistic regression model for FMD <6.5%.ConclusionsThe values of the analyzed biochemical and clinical factors (except for the reduced HDL fraction), the lack of inflammatory factor activity, and the increased S1P concentration indicate the dominance of antiatherosclerotic activity in this population. FMD and IMT are preserved, which suggests that the risk of early atherosclerotic changes in this group is comparable to the remaining population.